Quantification of circulating endothelial progenitor cells using the modified ISHAGE protocol. - Caroline Schmidt-Lucke (Public Library of Science (PLoS), 2010)
Aims Circulating endothelial progenitor cells (EPC), involved in endothelial regeneration, neovascularisation, and determination of prognosis in cardiovascular disease can be characterised with functional assays or using immunofluorescence and flow cytometry. Combinations of markers, including CD34+KDR+ or CD133+KDR+, are used. This approach, however may not consider all characteristics of EPC. The lack of a standardised protocol with regards to reagents and gating strategies may account for the widespread inter-laboratory variations in quantification of EPC. We, therefore developed a novel protocol adapted from the standardised so-called ISHAGE protocol for enumeration of haematopoietic stem cells to enable comparison of clinical and laboratory data. Methods and results In 25 control subjects, 65 patients with coronary artery disease (CAD; 40 stable CAD, 25 acute coronary syndrome/acute myocardial infarction (ACS)), EPC were quantified using the following approach: Whole blood was incubated with CD45, KDR, and CD34. The ISHAGE sequential strategy was used, and finally, CD45(dim)CD34(+) cells were quantified for KDR. A minimum of 100 CD34(+) events were collected. For comparison, CD45(+)CD34(+) and CD45(-)CD34(+) were analysed simultaneously. The number of CD45(dim)CD34(+)KDR(+) cells only were significantly higher in healthy controls compared to patients with CAD or ACS (p = 0.005 each, p<0.001 for trend). An inverse correlation of CD45(dim)CD34(+)KDR(+) with disease activity (r = -0.475, p<0.001) was confirmed. Only CD45(dim)CD34(+)KDR(+) correlated inversely with the number of diseased coronaries (r = -0.344; p<0.005). In a second study, a 4-week de-novo treatment of atorvastatin in stable CAD evoked an increase only of CD45(dim)CD34(+)KDR(+) EPC (p<0.05). CD45(+)CD34(+)KDR(+) and CD45(-)CD34(+)KDR(+) were indifferent between the three groups. Conclusion Our newly established protocol adopted from the standardised ISHAGE protocol achieved higher accuracy in EPC enumeration confirming previous findings with respect to the correlation of EPC with disease activity and the increase of EPC during statin therapy. The data of this study show the CD45(dim) fraction to harbour EPC.